Predictive Value of SYN-1 Levels for Mortality in Sepsis Patients in the Emergency Department - Hu L; Wang J; Zhang Y; Wang J; Wei B (Journal of Inflammation Research, 2024)
Le Hu,1– 3 Jia Wang,1– 3 Ye Zhang,1– 3 Junyu Wang,1– 3 Bing Wei1– 3 1Emergency Medical Center, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Beijing Key Laboratory of Cardiopulmonary Cerebral Resuscitation, Beijing, People’s Republic of China; 3Clinical Center for Medicine in Acute Infection, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Bing Wei; Junyu Wang, Email dr_weibing@126.com; wangjunyu_cyyy@126.comObjective: To evaluate and predict adverse outcomes associated with serum Syndecan-1 (SYN-1) levels in patients with early sepsis, and to explore the prognostic risk factors in sepsis and septic shock.Methods: This retrospective single-center observational study included 168 sepsis patients admitted to the Emergency Department of Beijing Chao-Yang Hospital Shijingshan Branch, Capital Medical University, from October 2020 to October 2021. Patients were categorized into sepsis (n=114) and septic shock (n=54) groups based on Sepsis 3.0 criteria. They were further divided into survival (n=128) and death (n=40) groups. Comparative analyses included general demographics and laboratory findings (SYN-1, lactic acid [LAC], procalcitonin [PCT], C-reactive protein [CRP]) within 3 hours of admission, as well as Acute Physiology and Chronic Health Evaluation II (APACHE II) and Sequential Organ Failure Assessment (SOFA) scores. Statistical methods included receiver operating characteristic (ROC) curve analysis, correlation analysis, and logistic regression.Results: Serum SYN-1 levels were significantly higher in the septic shock group (138.89± 9.26) compared to the sepsis group (102.89± 8.97) (P < 0.05). SYN-1 levels were also significantly higher in the death group (150.19± 7.65) compared to the survival group (103.301± 86.59) (P < 0.05). The area under the ROC curves for SYN-1, LAC, and APACHE II scores in predicting 28-day mortality were 0.668, 0.641, and 0.666, respectively. SYN-1 showed a positive correlation with SOFA scores (correlation coefficient=0.228). SYN-1, APACHE II score, and LAC were identified as independent risk factors for 28-day mortality in sepsis patients.Conclusion: SYN-1 demonstrates high sensitivity and specificity in early prediction of poor outcomes in sepsis patients. SYN-1, APACHE II score, and LAC serve as independent risk factors for 28-day mortality in sepsis patients.Keywords: Syndecan-1, sepsis, septic shock